Update of the list of qualified presumption of safety (QPS) recommended microbiological agents intentionally added to food or feed as notified to EFSA 18: Suitability of taxonomic units notified to EFSA until March 2023 - EFSA Panel on Biological Hazards (BIOHAZ); Konstantinos Koutsoumanis; Ana Allende; Avelino Alvarez‐Ordóñez; Declan Bolton; Sara Bover‐Cid; Marianne Chemaly; Alessandra De Cesare; Friederike Hilbert; Roland Lindqvist; Maarten Nauta; Romolo Nonno; et al. (EFSA Journal)
Abstract The qualified presumption of safety (QPS) approach was developed to provide a regularly updated generic pre‐evaluation of the safety of microorganisms, intended for use in the food or feed chains, to support the work of EFSA's Scientific Panels. The QPS approach is based on an assessment of published data for each agent, with respect to its taxonomic identity, the body of relevant knowledge and safety concerns. Safety concerns identified for a taxonomic unit (TU) are, where possible, confirmed at the species/strain or product level and reflected by ‘qualifications’. In the period covered by this Statement, no new information was found that would change the status of previously recommended QPS TUs. Of 38 microorganisms notified to EFSA between October 2022 and March 2023 (inclusive) (28 as feed additives, 5 as food enzymes, food additives and flavourings, 5 as novel foods), 34 were not evaluated because: 8 were filamentous fungi, 4 were Enterococcus faecium and 2 were Escherichia coli (taxonomic units that are excluded from the QPS evaluation) and 20 were taxonomic units (TUs) that already have a QPS status. Three of the other four TUs notified within this period were evaluated for the first time for a possible QPS status: Anaerobutyricum soehngenii, Stutzerimonas stutzeri (former Pseudomonas stutzeri) and Nannochloropsis oculata. Microorganism strain DSM 11798 has also been notified in 2015 and as its taxonomic unit is notified as a strain not a species, it is not suitable for the QPS approach. A. soehngenii and N. oculata are not recommended for the QPS status due to a limited body of knowledge of its use in the food and feed chains. S. stutzeri is not recommended for inclusion in the QPS list based on safety concerns and limited information about the exposure of animals and humans through the food and feed chains.